PERENCANAAN SISTEM JARINGAN DISTRIBUSI AIR BERSIH (STUDI KASUS DESA PANCA AGUNG KABUPATEN BULUNGAN) - Rachel Zandra Singal; Nur Azilz Jamal (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2022)
The need for clean water for the people of Panca Agung Village currently still relies on rainwater, well water and nearby water sources. This condition became the background in conducting research related to the planning of the clean water distribution network system for the Panca Agung village community. The purpose of this research is to determine the need for clean water based on population growth projections, to plan a pipe network system and to know the dimensions of the Broncaptering building that is able to serve the population's clean water needs. Analysis of water needs based on population growth projections to find out the discharge of clean water needs, clean water networks using Epanet 2.0 and analysis of the capacity of Broncaptering raw water catcher buildings needed. The results of the analysis of population growth projections for the next 10 years are calculated using the geometric method as many as 2.953 people and the clean water needs of Panca Agung Village are 2,584 liters/second until 2031. The available raw water debit is 123 liters/second so that it can meet the raw water needs of the village community. Clean water system planning is done by capturing water from water sources using a broncaptering building, broncaptering capacity of 3 x 2 x 1.5 M3, then distributed by gravity system to the reservoir based on the analysis of the clean water distribution piping system, using Epanet 2.0. The pipes used are HDPE types with diameters of 6, 4 and 2 inches with lengths according to segments. Kebutuhan air bersih masyarakat Desa Panca Agung saat ini masih mengandalkan air hujan, air sumur dan sumber air terdekat. Kondisi ini menjadi latar belakang dalam melakukan penelitian terkait perencanaan sistem jaringan distribusi air bersih untuk masyarakat desa Panca Agung. Tujuannya penelitian adalah mengetahui kebutuhan air bersih berdasarkan proyeksi pertumbuhan penduduk, merencanakan sitem jaringan pipa serta mengetahui dimensi bangunan Broncaptering yang mampu melayani kebutuhan air bersih penduduk. Analisa kebutuhan air berdasarkan proyeksi pertumbuhan penduduk untuk megetahui debit kebutuhan air bersih, jaringan air bersih menggunakan Epanet 2.0 dan analisa kapasitas bangunan penangkap air baku Broncaptering yang dibutuhkan. Hasil analisa proyeksi pertumbuhan penduduk untuk 10 tahun kedepan dihitung menggunakan metode geometrik sebanyak 2.953 jiwa dan kebutuhan air bersih Desa Panca Agung yaitu 2,584 liter/detik hingga tahun 2031. Debit air baku yang tersedia sebesar 123 liter/detik sehingga dapat memenuhi kebutuhan air baku masyakat Desa Panca Agung. Perencanaan sistem air bersih dilakukan dengan cara menangkap air dari sumber air dengan menggunakan bangunan broncaptering, kapasitas broncaptering 3 x 2 x 1,5 M3, kemudian disalurkan dengan sistem gravitasi ke reservoir berdasarkan hasil analisa sistem perpipaan distribusi air bersih, menggunakan Epanet 2.0. Pipa yang digunakan adalah jenis HDPE dengan diameter 6, 4 dan 2 inch dengan panjang sesuai segmen.